Voluntary disclosure in asymmetric contests - Christian Ewerhart; Julia Lareida (University of Zurich, Department of Economics, 2023)
This paper studies the incentives for interim voluntary disclosure of verifiable information in probabilistic all-pay contests with two-sided incomplete information. Private information may concern marginal cost, valuations, and ability. Our main result says that, if the contest is uniformly asymmetric, then full revelation is the unique perfect Bayesian equilibrium outcome. This is so because the weakest type of the underdog reveals her type in an attempt to moderate the favorite while, similarly, the strongest type of the favorite tries to discourage the underdog - so that the contest unravels. This strong-form disclosure principle is robust with respect to correlation, partitional evidence, randomized disclosures, sequential moves, and continuous type spaces. Moreover, the assumption of uniform asymmetry is not needed when incomplete information is one-sided. However, the principle breaks down when contestants are potentially too similar in strength, possess commitment power, or when information is unverifiable. In fact, cheap talk will always be ignored, even if mediated by a trustworthy third party.
Keywords: C72; D74; D82; J71; 330; Asymmetric contests; Incomplete information; Disclosure; Strategic complements and substitutes; Dominance and defiance; Cheap talk